Industrial Sustainability Policy and Standards-Related on Management Discipline of SMEs Industry in Malaysia: A Conceptual Framework - Nur Qurratul Ain, Adanan; Faiz, Mohd Turan; Kartina, Johan (Springer, 2021)
Since a demands of sustainability practice implementation, the growing countries especially Malaysia using the sustainability tools to comply sustainable development goals. For the SMEs Malaysia industry, it is essential to develop a suitable sustainable assessment tool as a linking gap between the governor and the practitioner. Thus, this research will deal with a new development of the tool for assessing sustainability management in the context of Malaysian industry as a medium to assess the sustainability practices of project compliances performance. This method will use the integration of Industrial practices for a new cluster rating that refer to ISO standards and UN SDG policy as a guideline to quantify the sustainability compliances of the industry. This assessment will help the industry especially the policy-maker to measure the critical element of sustainability compliance. Hence the conceptual framework of this research is a guide mechanism for the development tool which acts as sustainability indicator that will simplify the assessment of the sustainable performance for decision making and attitudinal.